The Morphological Deformations and Discrepancy in Sex Ratio in Goldfish (Carassius Auratus) As Biomarker for Pollution in Al- Hammar Marshes – South Iraq - Huda Hassan (University of Thi-Qar Journal of Science, 2019)
The present study include determine the morphological anomalies and sex ratio disruption for gold fish Carassiusauratus that captured from Al-Hammar marshes during study period that prolonged from October 2013 to May 2014 .the number of captured fish were 106. Morphological anomalies were represent ell by deformity of vertebral column(curved and fusion of vertebrae ) ,face and upper jaws , fin erosion , popeye and eye bleeding . Sex ratio tend stronglytowed females (1;25.5).